2005
DOI: 10.1089/oli.2005.15.183
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation to Polyethylene Glycol Polymer Promotes Aptamer Biodistribution to Healthy and Inflamed Tissues

Abstract: Here, we examine biodistribution of radiolabeled aptamers and assess the relative ability of different stabilized aptamer compositions (mixed 2'-F/2'-O-Me; fully 2'-O-Me modified) to access inflamed tissues in a murine inflammation model. Biodistribution of 3H-labeled aptamers, including pegylated and unpegylated compositions, was assessed 3 hours postadministration using quantitative whole body autoradiography (QWBA). Aptamer penetration of cells in kidney and liver was also examined at a qualitative level by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 22 publications
1
36
1
Order By: Relevance
“…This result is in accordance with previous studies which showed that aptamers are not able to cross the BBB passively [35][36][37]. There were no significant differences between the two HER2 aptamers and the negative control aptamer, except a significant increase in kidney uptake for the negative control aptamer, which may be related to the difference in nucleotide sequence and therefore difference in hydrophilicity.…”
Section: Tissue Biodistributionsupporting
confidence: 92%
“…This result is in accordance with previous studies which showed that aptamers are not able to cross the BBB passively [35][36][37]. There were no significant differences between the two HER2 aptamers and the negative control aptamer, except a significant increase in kidney uptake for the negative control aptamer, which may be related to the difference in nucleotide sequence and therefore difference in hydrophilicity.…”
Section: Tissue Biodistributionsupporting
confidence: 92%
“…The spatiotemporal control of drug delivery afforded by our approach may enhance the efficacy and therapeutic index of many drugs. Our strategy involves less synthetic workup than approaches that change oligonucleotide biodistribution via chemical modification (e.g., PEGylation) (14,(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…However, unmodified oligonucleotides are susceptible to hydrolysis by nucleases, limiting their potential for in vivo biomedical applications. To improve aptamers' function as tumor-targeting ligands, various chemical modifications for enhancing their stability have been introduced [28][29][30][31][32]. Among these modification methods, phosphate backbone modification with phosphorothioate is a promising strategy, since it does not hamper the target-binding affinity of the oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%